NGHIÊN CỨU THÀNH PHẦN FLAVONOIT VÀ MEGASTIGMAN GLUCOSIT CỦA CÂY GÀO (FICUS CALLOSA) - Kiệm, Phan Văn; Minh, Châu Văn; Cường, Nguyễn Xuân; Thuý Hằng, Đan Thị; Thảo, Nguyễn Phương; Nam, Nguyễn Hoài; Bản, Ninh Khắc; Hải, Trương Nam (Vietnam Journal of Chemistry, 2012)
Chromatographic separation led to the isolation of two flavonoid glycosides, glucotricin (1) and rhoifolin (2), and one megastigmane glycoside, corchoionoside C (3), from the leaves of Ficus callosa. Their structures were elucidated by ESI-MS and NMR experiments. This is the first report of these compounds from F. callosa. Key words: Ficus callosa, Moraceae, glucotricin, rhoifolin.